'It's a whole cultural shift': understanding learning in cultural commissioning from a qualitative process evaluation. Issue 1 (2nd January 2021) - D, Crone; L, Ellis; H, Bryan; M, Pearce; J, Ford
ABSTRACT: This qualitative process evaluation investigated learning from stakeholders (patient representatives, art managers/artists, clinicians and commissioners) involved in a co-produced cultural commissioning grant scheme. The scheme was devised as a mechanism to foster learning between, and within, stakeholder groups and to embed co-production in decision-making in clinical commissioning. The evaluation included respondents (n = 36) from four stakeholder groups in three sequential stages. Findings identified themes centred on outcomes, learning, co-production, and cultural and political change, specifically that stakeholder roles need to be clearly defined and understood and that co-production takes a significant time commitment. Co-production in innovative projects is both complex and challenging. However, despite this, involving stakeholders has benefits for service design and the clinical commissioning process.